Nuclear export signal within CALM is necessary for CALM‐AF10‐induced leukemia. Issue 3 (13th February 2014) - Suzuki, Mai; Yamagata, Kazutsune; Shino, Mika; Aikawa, Yukiko; Akashi, Koichi; Watanabe, Toshio; Kitabayashi, Issay
<x xml:space="preserve">Abstract</x> The CALM–AF10 fusion gene, which results from a t(10;11) translocation, is found in a variety of hematopoietic malignancies. Certain HOXA cluster genes and MEIS1 genes are upregulated in patients and mouse models that express CALM‐AF10. Wild‐type clathrin assembly lymphoid myeloid leukemia protein (CALM) primarily localizes in a diffuse pattern within the cytoplasm, whereas AF10 localizes in the nucleus; however, it is not clear where CALM‐AF10 acts to induce leukemia. To investigate the influence of localization on leukemogenesis involving CALM‐AF10, we determined the nuclear export signal (NES) within CALM that is necessary and sufficient for cytoplasmic localization of CALM‐AF10. Mutations in the NES eliminated the capacity of CALM‐AF10 to immortalize murine bone‐marrow cells in vitro and to promote development of acute myeloid leukemia in mouse models. Furthermore, a fusion of AF10 with the minimal NES can immortalize bone‐marrow cells and induce leukemia in mice. These results suggest that during leukemogenesis, CALM‐AF10 plays its critical roles in the cytoplasm.